Front Cover. Issue 4 (11th March 2020) - Pascual‐Alonso, Ainhoa; Blasco, Laura; Vidal, Silvia; Gean, Esther; Rubio, Patricia; O'Callaghan, Mar; Martínez‐Monseny, Antonio F.; Castells, Alba Aina; Xiol, Clara; Català, Vicenç; Brandi, Nuria; Pacheco, Paola; et al.
Abstract: The cover image is based on the Original Article Molecular characterisation of Spanish patients with MECP2 duplication syndrome by Ainhoa Pascual‐Alonso et al., https://doi.org/10.1111/cge.13718 . Abstract : The cover image is based on the Original Article Molecular characterisation of Spanish patients with MECP2 duplication syndrome by Ainhoa Pascual‐Alonso et al., https://doi.org/10.1111/cge.13718 .